The Problem of Independence and Effectiveness of Arbitration in the Indonesian Legal System: An Analysis of the Position of Arbitral Awards and Their Enforcement Mechanisms - Risna Dayanti; Maisa Faizahra Ramadhani; Dilla Pratiwi; Nurul Hidayah Ritonga; Mellysa Putri Lestari (ISNU Sumatera Utara, 2024)
Arbitration has become one of the growing dispute resolution mechanisms in the Indonesian legal system because it offers a more flexible, fast, and confidential process than litigation resolution. However, behind the strengthening of the position of arbitration through Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, there are still issues regarding the independence of arbitration and the effectiveness of the implementation of its award, especially because of the court's involvement in the process of recognition and execution of arbitral awards. This research aims to analyze the position of arbitration in the Indonesian legal system and examine various problems that affect the effectiveness of the implementation of arbitral awards, especially related to the relationship between arbitration authority and judicial institutions. This study uses a normative juridical method with a legislative approach, a conceptual approach, and a case approach. Research data was obtained through a literature study of laws and regulations, legal doctrines, academic literature, and court decisions related to the recognition and execution of arbitral awards. The results of the study show that arbitration has gained strong legitimacy as an alternative dispute resolution mechanism, but its effectiveness still faces obstacles in the implementation stage of awards due to dependence on the courts, differences in legal interpretation, and institutional challenges of arbitration. The conclusion of this study emphasizes that strengthening arbitration in Indonesia not only requires adequate regulation, but also harmonization of the relationship between arbitration and the court as well as improving the professionalism of arbitration institutions to ensure legal certainty and the effectiveness of dispute resolution.